THE SOCIETY OF MINANGKABAU IN TULIS SUTAN SATI’S SENGSARA MEMBAWA NIKMAT: BETWEEN LOCAL TRADITIONS AND ISLAMIC TEACHINGS - Betty Mauli Rosa Bustam (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The culture of Minangkabau is diffrent from the ones generally existing in Indonesia,particularly compared to the Javanese culture. Therefore, the culture of Minangkabau is often considered as a contradictory or antithesis of the Javanese culture, often represented as the overall culture of Indonesia. Minangkabau culture peculiarity lays in its matrilineal which inflences lineage and inheritance. The contradictory matter refers to the society of Minangkabau that is the largest Islamic followers in Indonesia, yet their ancestral traditions are not completely in line with the Islamic teachings, some even are contradictory. It is a common knowledge that a literary work is not born from an ‘empty culture’ meaning that a literary work must be inflenced by its author. Even some of literary experts believe that a society described in a novel is the real society where the author lives. It is similar to the novel of Sengsara Membawa Nikmat of Sutan Sati, which is the object of this study. The novel describes the society of Minangkabau in the early 20th century, at the end of 1920s to be exact.This research shows how the effrts of Minangkabau people in adopting the Islamic teachings completely and how Islam adapts to the Minangkabau hereditary traditions. Some of the traditions may exist in accordance with the Islamic teachings, but some do not. Even to gather all headman of the ethnic group to decide a case is not in line with Islam, whether following pure traditions or Islam as it should be.